Implementasi Ekonomi Hijau dalam Meningkatkan Koordinasi Keuangan Pusat-Daerah: Studi Kasus Pemerintah Kota Surabaya - Rayi Septiana Afifa; Ivana Jolie Firginia; Eva Hany Fanida; Melda Fadiyah Hidayat (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
The transition toward a green economy requires strong fiscal synchronization between central and local governments. This study aims to analyze fiscal coordination in supporting green economy policies in Surabaya City during the 2021–2024 period. Employing a descriptive quantitative approach with content analysis of Budget Realization Reports (LRA), this study evaluates the trends of Local Original Revenue (PAD) and Transfer Revenue within the framework of green budgeting. The results indicate that Surabaya City possesses high fiscal independence, with PAD realization consistently averaging above IDR 5 trillion per year, providing the flexibility to independently fund green innovations. Furthermore, the implementation of Law No. 1 of 2022 (HKPD) has proven to strengthen fiscal coordination, where green budgeting serves as a catalyst for Surabaya's economic growth of 5.87%. This study concludes that strengthening regional fiscal capacity is an absolute prerequisite for the sustainability of the low-carbon economic transition at the local level. These findings serve as a vital reference for other regions in optimizing financial instruments to achieve ecological targets.